The Impact of Siblings on the Geographic Distance Between Adult Children and Their Ageing Parents. Does Parental Need Matter?. Issue 6 (17th March 2017) - van den Broek, Thijs; Dykstra, Pearl A.
Abstract: Research consistently shows that children with siblings live at a greater distance from their parents than do only children. We extend this literature by assessing whether this difference varies as a function of parental need. Multinomial logistic regression analyses of German Ageing Survey data enriched with indicators at the district (Nomenclature of Statistical Territorial Units level three) level ( n = 2, 028) show that, in general, children with a sibling are less likely than only children to share a household with a parent. We do not find that children with a sibling are more likely than only children to live at great distance, that is, more than 2 hours away, from their parents. The differences between only children and children with siblings in parent–child proximity are most pronounced when parents are coping with severe health limitations. It is well established that only children are more likely than children with siblings to provide support and care to ageing parents. Our findings suggest that, in addition, only children might be more compelled than their counterparts with siblings to adjust their living arrangements in order to facilitate caregiving when parent care needs manifest themselves. Copyright © 2017 John Wiley & Sons, Ltd.